Key concepts in learning disabilities - Talbot, Pat.; Astbury, Geoff; Mason, Tom, 1950-2011.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2010)
This is a handy guide to the topics you need to know about whether studying or working in the field of learning disabilities. The A-Z format allows you to 'dip in' and quickly find relevant information on topics ranging from autism to rights and from advocacy to challenging behaviours.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Learning disabilities; Electronic books